What do we know about the future of maize value chains in a changing climate and agri-food system? - Tesfaye, Kindie; Sonder, Kai; Pequeno, Diego; Hartley, Faaiqa; Gbegbelegbe, Sika (CGIAR, 2024)
Key messages • Population growth, changing diets, and a rapidly growing feed sector are contributing to a sharp increase in global maize demand which is expected to double by 2050 relative to 2010. • Average global maize yield is projected to decrease by 11% under a global warming scenario of 2.0 °C (2060-2084) relative to the 1986–2005 period (in the absence of technological change, adaptation, or market adjustments). • The feed demand for maize is expected to grow faster in the coming few decades largely driven by rapid economic growth and diet shifts in highly populated regions in Asia, the Middle East, and Latin America. • Meeting the growing demand for maize will require dramatic increases in production, marketing, utilization, and resilience of maize-based farming systems. • While the supply of maize over the coming decades will be constrained by climate change, and limited availability of land and water, technological and policy innovations will bring new opportunities. • The combined challenges of increasing food demand, persisting poverty and malnutrition, natural resource depletion, and climate change will require the world to double the productivity and boost the sustainability and resilience of maize-based farming systems within planetary boundaries.